Modernisasi Infrastruktur Sekolah dalam Meningkatkan Motivasi Belajar Siswa di SMK Negeri 2 Somolo-Molo - Lombu, Kardiaman; Harefa, Hendrikus Otniel Nasozaro; Harefa, Anugerah Tatema; Lase, Fatiani (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyse the role of school infrastructure modernisation in improving student learning motivation at SMK Negeri 2 Somolo-molo and to identify the factors that have prevented its optimal implementation. The research used a qualitative method with a descriptive approach, with the research subjects including the principal, teachers, and students. Data collection was carried out through observation, in-depth interviews, and documentation, then analysed using data reduction, data presentation, and conclusion drawing techniques, accompanied by source triangulation to ensure data validity. The results of the study show that infrastructure modernisation has been carried out through the construction of an auditorium, renovation of classrooms, construction of a teachers' office, and the provision of learning facilities such as tables, chairs, whiteboards, and smart TVs. This modernisation has had a positive impact on increasing student motivation, interest and attitude towards learning, and has helped teachers deliver learning materials more effectively. However, the implementation of school infrastructure modernisation has not been optimal due to budget constraints and the geographical constraints of schools located in disadvantaged areas, which have hampered the procurement of facilities and infrastructure and slowed down the construction process